A new species of Trachycephalus (Amphibia, Anura, Hylidae) from the State of Goiás, Brazil - Cintra, Carlos Eduardo Domingos; Silva, Hélder Lúcio Rodrigues; Da Silva Jr., Nelson Jorge; de Anchietta Garcia, Paulo Christiano; Zaher, Hussam (Zootaxa, 2009)
A new species of Trachycephalus is described for the Cerrado biome of Goiás, Brazil. Trachycephalus mambaiensis sp. nov. is distinguished from the other ten species of the genus by the skin co-ossified with the skull, heavy cranial ossification, frontoparietal that fails to articulate with squamosal, absence of a crista occipitalis and secreting glands of milky and viscous substances. The skull of the new species shows an intermediary condition between species of Trachycephalus with a well ossified skull (Casque-headed frogs) and those without cranial ossification.